Anti-fertility effect of ethanol extract of lerak (Sapindus rarak DC) fruits in female Sprague Dawley Rats - INARAH FAJRIATY; HARIYANTO I. H.; YOUNGKY HARYANTO (Nusantara Bioscience, 2017)
Fajriaty I, Hariyanto I.H, Haryanto Y. 2017. Anti-fertility effect of ethanol extract of lerak (Sapindus rarak DC) fruits in female Sprague Dawley Rats. Nusantara Bioscience 9: 102-106. This research aims to observe the antifertility effect of ethanol extract of Lerak fruits (SFEE) in female sprague dawley rats. Group of rats are divided into four groups, the first group is given carboxymethyl cellulose (CMC) as negative control (KN), the second group is given ethinylestradiol as positive control (KP), the third group is given SFEE with dose 50 mg/kg BW, and the fourth group is given SFEE with dose 100 mg/kg BW. The female rats in estrus phase is mated with male rats. In plug vaginal checking and smear vaginal there is sperm that signify if female rats have experienced copulation and currently on the day of the zero pregnancy. All treatment are given orally from 0 day of pregnancy to 10th day of pregnancy. Antifertility effect on treatment in rats is shown from laparotomy in the 20th day of pregnancy. Determining of the antifertility effect that to do include pre-implantation loss effect and post implementation loss effect. The result of this research shows that SFEE with dose 50 mg/kg BW has antifertility effect that is pre-implantation loss as big as 0% and post-implantation loss as big as 10.53% and SFEE with dose 100 mg/kg BW shows antifertility effect is pre-implantation loss and post implantation loss in each of 47.50% and 28.57%. This observation shows that SFEE has antifertility effect.